Discriminating Ficus deltoidea var. bornensis from different localities by HPTLC and FTIR fingerprinting - Khamsah Suryati, Mohd; Nashriyah, Mat; Saravanan, A Dharmaraj (2014)
A nondestructive, efficient, and accurate fingerprinting method using Fourier transform infrared spectroscopy (FTIR) has been developed and optimized for the investigation and demonstration of the variance in chemical characteristics among extracts of Ficus deltoidea Jack var. bornensis from different but closely situated origins. The capacity of attenuated total reflectance (ATR) to differentiate these samples were studied using methanol and water extracts which were preliminarily screened using HPTLC with vitexin and isovitexin being used as markers for authentication. The mobile phase used was ethyl acetate: formic acid (0.1%): methanol at ratio of 5:5:2 (v/v/v) and the profile showed that methanol extracts had higher affinity for the markers. The FTIR spectra indicated that there was no obvious difference in spectroscopic pattern for either extracts when comparing samples from different localities but the absorption intensities of some peaks were different. Multivariate statistical analyses of PCA and HCA showed that both these techniques were capable of identifying the most similar as well as most differing samples and the identification depended on the type of extract. Overall, FTIR fingerprinting has the potential to be a fast and reliable analytical methodology for the discrimination between variants of plant from closely situated locations and hence chemically similar samples.